Biogeographic history of a large clade of ectomycorrhizal fungi, the Russulaceae, in the Neotropics and adjacent regions. Issue 2 (30th July 2022) - Hackel, Jan; Henkel, Terry W.; Moreau, Pierre‐Arthur; De Crop, Eske; Verbeken, Annemieke; Sà, Mariana; Buyck, Bart; Neves, Maria‐Alice; Vasco‐Palacios, Aída; Wartchow, Felipe; Schimann, Heidy; Carriconde, Fabian; et al.
Summary: The biogeography of neotropical fungi remains poorly understood. Here, we reconstruct the origins and diversification of neotropical lineages in one of the largest clades of ectomycorrhizal fungi in the globally widespread family Russulaceae. We inferred a supertree of 3285 operational taxonomic units, representing worldwide internal transcribed spacer sequences. We reconstructed biogeographic history and diversification and identified lineages in the Neotropics and adjacent Patagonia. The ectomycorrhizal Russulaceae have a tropical African origin. The oldest lineages in tropical South America, most with African sister groups, date to the mid‐Eocene, possibly coinciding with a boreotropical migration corridor. There were several transatlantic dispersal events from Africa more recently. Andean and Central American lineages mostly have north‐temperate origins and are associated with North Andean uplift and the general north–south biotic interchange across the Panama isthmus, respectively. Patagonian lineages have Australasian affinities. Diversification rates in tropical South America and other tropical areas are lower than in temperate areas. Neotropical Russulaceae have multiple biogeographic origins since the mid‐Eocene involving dispersal and co‐migration. Discontinuous distributions of host plants may explain low diversification rates of tropical lowland ectomycorrhizal fungi. Deeply diverging neotropical fungal lineages need to be better documented.